Critical reading and writing for postgraduates - Wallace, Mike; Wray, Alison (Los Angeles SAGE, 2016)
"Reading critically, and writing using critical techniques, are crucial skills you need to apply to your academic work. Practical and engaging, Critical Reading and Writing for Postgraduates is bursting with tools for analysing texts and structuring critical reviews, helping you to gradually build your skills beyond undergraduate level and gain confidence in your ability to critically read and write." -- Provided by publisher.
Part One: Becoming a critical reader and self-critical writer -- 1. What it means to be critical -- 2. Making a critical choice -- 3.A first look: interrogating abstracts -- 4. Getting started on critical reading -- 5. Getting started on self-critical writing -- 6. Creating a comparative critical summary -- Part Two: Developing an in-depth analysis -- 7.A mental map for navigating the literature -- 8. Tools for thinking and ways of thinking -- 9. Reasons for conducting the research -- 10. Knowledge claims and their key characteristics -- 11. Developing a critical analysis of a Text -- 12.A worked example of a critical analysis -- 13. Developing your argument in writing a critical review of a text -- Part Three: Putting your critical reviews to work -- 14. Focusing and building up your critical literature review -- 15. Integrating critical literature reviews into your dissertation -- 16. Critical literature reviews in alternative dissertation structures note continued: 17. Tools for structuring a dissertation -- 18. Using the literature in research papers and oral presentations.
Includes bibliographical references and index.
Keywords: Reading (Higher education).; Critical thinking -- Study and teaching (Higher)